2017
DOI: 10.3732/ajb.1700054
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Quaternary migration patterns in the Bahamian archipelago: Evidence from theZamia pumilacomplex at the northern limits of the Caribbean island biodiversity hotspot

Abstract: Despite changes in migration patterns with global climate, expected heterozygosity with both marker systems remains within the range reported for cycads, but with significant levels of increased inbreeding detected by the microsatellites. This finding is likely associated with reduced gene flow between and within paleo-provinces, accompanied by genetic drift, as rising seas enforced isolation. Our study highlights the importance of the maintenance of the predominant direction of genetic exchange and the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 120 publications
(141 reference statements)
1
5
0
Order By: Relevance
“…D1-D4). This is in accordance with previous findings by Caputo et al (2004), who found all characters from an extensive morphological and micromolecular data set to be homoplastic, as well as with inferences from population-based studies in the Caribbean clade (Salas-Leiva et al 2017;Meerow et al 2018). The rampant homoplasy pervasive in the genus has resulted in several species that share morphological resemblance but that are not closely related.…”
Section: Ancestral Character States and Homoplasy Of Macromorphologicsupporting
confidence: 92%
See 2 more Smart Citations
“…D1-D4). This is in accordance with previous findings by Caputo et al (2004), who found all characters from an extensive morphological and micromolecular data set to be homoplastic, as well as with inferences from population-based studies in the Caribbean clade (Salas-Leiva et al 2017;Meerow et al 2018). The rampant homoplasy pervasive in the genus has resulted in several species that share morphological resemblance but that are not closely related.…”
Section: Ancestral Character States and Homoplasy Of Macromorphologicsupporting
confidence: 92%
“…Of the markers used, seven (40S, ATG2, GroES, HTS, LiSH, PEX4, PMP22, WRKY4) were identified and developed in our laboratories (Salas-Leiva et al 2014); the remaining ones (CyAG, psbK/I) were derived from previous publications (table 2). The loci 40S, ATG2, CyAG, and GroES were previously used to infer the generic relationships of the Cycadales (Salas-Leiva et al 2013), and 40S, ATG2, CyAG, GroES, LiSH, PEX4, and WRKY4 were applied to assess the genetic diversity and genetic structure of Bahamian zamias (Salas-Leiva et al 2017). The single chloroplast gene locus included in the study (psbK/I) was selected because it had displayed the best performance (amplification success and high no.…”
Section: Marker Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climatic changes during the Quaternary have been implicated in demographic, biogeographic, and genetic changes among populations, potentially leading to speciation (Hewitt, ). Pleistocene glacial cycles, specifically, have been shown to affect the distribution of taxa (McCormack et al., ; Gugger et al., ; Salas‐Leiva et al., ) and drive speciation (Carstens and Knowles, ; Levsen et al., ). Data compiled by Toledo () indicate that vegetation types have shifted in tropical Mexico during Pleistocene glacial cycles creating the potential for such processes in this region.…”
mentioning
confidence: 99%
“…"Tiloo Cay", possess distinctly narrower, broader, or more coriaceous leaflet phenotypes than Zamia on other Bahamian islands. Genetic analysis of Bahamian Zamia populations [69] supports the possibility of extended genetic isolation of the Long Island Z. lucayana population, but not of the Eleuthera and Tiloo Cay Zamia populations. In this case, genetic patterns in Pharaxonotha mirror the phenoptypic traits displayed by their host Zamia better than the genetic analysis of the Zamia populations themselves.…”
Section: Independent Tests Of Beetle Generated Hypothesesmentioning
confidence: 86%